PENGARUH MOTIVASI DAN PENGETAHUAN TERHADAP MINAT INVESTASI DI PASAR MODAL - Richo Elfrizal Sabda Ar Rahman; Waspodo Tjipto Subroto (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2022)
Managing personal finances is not an easy thing for students due to the growing phenomenon of consumptive behavior. Even though they have been equipped with knowledge through courses on financial institutions and capital markets, students seem desperate to invest in the capital market due to several factors. This study aims to explain the effect of motivation and knowledge on interest in investing in the capital market in Students of the Economics Education Study Program, State University of Surabaya. This research uses quantitative methods. Determining the research population used a purposive sampling technique, namely students of the 2018 economics study program, a total of 62 students. Collecting data using a questionnaire. The analytical method uses multiple linear regression analysis. The results of this study indicate that there is a positive effect of motivation on investment interest in the capital market, there is a positive effect of knowledge on investment interest in the capital market and motivation and knowledge have a positive effect on investment interest in the capital market in Unesa Economics Education Study Program students.